Factors that influence UPV students' decision in taking the CPA board examination - Panaguiton, Benmar B.
The objective of this study is to know the factors that influence the UPV-CM students' decision in taking the CPA examination. A survey was made on the one hundred and twenty (120) BSA students who are to about to graduate this School Year 1998-99 of the College of Management, University of the Philippines in the Visayas, Iloilo City. Fifty (50) questionnaires were distributed to fifty (50) students using the simple random sampling technique. However, only thirty-seven (37) were returned and the researcher was not bale to follow those that were not returned due to time constraints. The study revealed that all respondents, except for one, have plans of taking the CPA examination. These respondents also established their intention to enroll in review classes in Manila. The review class, according to the respondents, would give them a better chances in passing the CPA examination. Review centers in manila were deemed to have a better method of reviewing the candidates and offer the best and the latest facilities for the review. certain factors that have a bearing on the students' decision, of taking the CPA examination or not, were confirmed in the study. These factors include the respondent's personal drive and the motivation they receive from other people like their classmates, friends and family members. Also, their economic conditions and their undergraduate academic preparation were positively identified to have an effect on such decision. The most influential factor that was revealed in this study is the personal drive of the students themselves in pursuing the accounting career. Most them have indicated that BSA was their first choice as a course, with being a CPA as a top reason in mind. Further, they have avowed that taking the CPA examination and becoming a CPA is their personal aspiration. Motivation and encouragement is also one of the many areas that was confirmed to influence the respondents' decision regarding the CPA examination. The motivation the respondents receive from other people-their classmates, peers relatives and mentors apart from their immediate family impel them to pursue the CPA profession. The respondents were asked to assess their capacity in passing the examination based on their academic performance in the University. Only a third of them confirmed that they could make it. Thus, they have affirmed that they need the review classes to supplement their undergraduate learning. The respondents' economic conditions were found to have an effect on their decision to take the examination, too. This is manifested by the respondents' declaration that only forty-three (43% of them will take the examination right after graduation and the others would have to wait a year later to look for possible sources of fund like employment. This study also made some suggestion on how to help the students in their pursuit of career in accounting. Some of the suggestions made were the institutionalization of review subjects in the curriculum and the offering of review classes during summer break. A "study-now, pay later" scheme was also recommended including the making of Iloilo as a test center for CPA examinations. CPAs were also encouraged to establish a review center in Iloilo City to serve the existing market of CPA candidates.